MOTIVASI PETANI DALAM PENERAPAN TEKNOLOGI PTT PADI SAWAH (Oryza Sativa L.) DI DESA GUNUNG SARI PROVINSI SULAWESI BARAT - Satriani, Satriani; Effendy, Lukman; Muslihat, Elih Juhdi (Jurnal Penyuluhan Pertanian, 2013)
The experiment was conducted for two months, starting from March 17 through May 12 in the village of Gunung Sari subdistrict Pasangkayu District North Mamuju West Sulawesi province. This study explains the motivation of farmers in applying technology SLPTT Rice (Oryza sativa L.) and the lowest indicators of technology implementation SLPTT Rice (Oryza sativa L.). Sampling method used: purposive sampling (sampling with intentional). Three group of farmers respondents drawn from each group of 10 farmers were taken. Data collection is done by using a questionnaire in the form of questions. The data that has been obtained tabulated and analyzed by using test concoordasi Kendall's W (SPSS version 18) and obtained the value of Cronbach's Alpha of its 0.806, then the instrument in the form of questions can be used to measure Farmers motivation in Application technology SL-PTT Rice (Oryza sativa L.). The results indicate that the farmers motivation in the Application Technology SL-PTT Rice (Oryza sativa L.) based on the analysis of non-parametric Kendall's W concordance obtained the highest rank, namely: I. Needs, with an average value of 2.73. II. Award, with an average value of 2.05 and III. Willingness, with an average rating 1.22.